O profissional da educação infantil e os cursos de licenciatura: desencontros na formação inicial - NASCIMENTO, SIMONE MARIA DE BASTOS (2015)
The discussion about the teacher professional formation is constant and long-standing in Brazilian context because their importance and consequences to pedagogic practices which are thought and implemented on different levels of teaching. Considering that Law of Directives and Bases of National Education 9394/1996 points to professional formation from any graduation course is enough to work on children education, the general objective of this research is to enquire what extent the initial professional formation from these graduation courses contemplates elements related to children education. Specific objectives are to recognize the teachers‟ initial professional formation who works into children education public institutions in the city of Guarapuava/PR, to identify knowledge learnt during initial professional formation, to analysis curricular grids of graduate courses of Center-West State University (UNICENTRO) enquiring what extent professional formation from these courses help teachers how to work on children education and to think about the currents laws, their consequences, determinations and challenges in teachers‟ professional formation to work on children education. Historically, young children education has been neglected by public politics as well as the teacher‟s professional formation to work on this level of teaching. Currently, with the inclusion of children education as a part of basic education and children‟s right, systematic efforts has been carried out, mainly by researchers, to understand and to think about special elements regarding teaching on this level. This research is qualitative and quantitative. It is based on an exploratory study about teachers‟ professional formation on children education working in some public institutions in the city of Guarapuava/PR and it analyzed curricular grids of 9 graduation courses in university at the same city. Reflections are based on teacher professional formation and children education by Gatti (2000, 2013), Kishimoto (2002), Kramer (2008), Kuenzer (2004), Shiroma, Oto e Moraes (2007) and other. Debates have presented points related to legislation that orient the teacher professional formation, its constitution and consequences as well as they have thought about specific elements on children education teaching. Data analysis presented as result that pedagogic work to zero-five-year-children does needs a qualified professional who must work to encourage the young children‟s development by way of interplays and organized and lived experiences. Besides, we understand that, although lawfully everybody who is graduated may work on children education, there are not contents, knowledge and debates about zero-five-year-children in specific graduation courses and it upsets the quality of the work developed. So we think that the professional formation on Pedagogy graduation course is able to provide minimally reflections about teacher‟s work on children education, even if it still is discreetly and insufficiently.